(untitled) (Research, Society and Development, 2023)
Introduction: The development of generalized muscle weakness related to the critical patient is one of the recurrent complications in patients admitted to an intensive care unit. The use of the cycloergometer has been shown to be a safe option for early mobilization,and can be used to recover the functional capacity of the critical patient. Objective: To review publications about the efficacy of the use of the cycloergometer in the proposal of early mobilization in intensive care unit patients. Method: A systematic review was carried out with search of articles in the Medline and SciELO database. The descriptors were: Physiotherapy, Intensive Care Unit and Rehabilitation in English and Portuguese. We included randomized clinical trials and case studies, with publication date from 2015 to 2019, with a title containing questions or words that indicate the approach of the use of the cycloergometer in the direct or indirect assistance of early mobilization in patients in the intensive care unit. Results: A total of 09 articles met the inclusion criteria, with a total of 782 participants. All the studies analyzed demonstrated that the use of the cycloergometer is safe and feasible in the early treatment of critically ill adult patients, and no deleterious effect has been reported in their technique of use. Conclusion: The use of the cycloergometer in a critical patient has the potential to aggregate to the Physical Therapy in the Intensive Unit, since it proves to be a safe, viable and preventive resource to the deleterious effects of hospitalization, such as muscle weakness, hypotrophy and functional capacity recovery.